2023
DOI: 10.3390/ph16111599
|View full text |Cite
|
Sign up to set email alerts
|

Brain Delivery of Cisplatin Using Microbubbles in Combination with Ultrasound as an Effective Therapy for Glioblastoma

Fumiko Hagiwara,
Daiki Omata,
Lisa Munakata
et al.

Abstract: Glioblastoma is a highly invasive and fatal disease. Temozolomide, a blood–brain barrier (BBB)-penetrant therapeutic agent currently used for glioblastoma, does not exhibit sufficient therapeutic effect. Cisplatin (CDDP), a versatile anticancer drug, is not considered a therapeutic option for glioblastoma due to its low BBB permeability. We previously investigated the utility of microbubbles (MBs) in combination with ultrasound (US) in promoting BBB permeability and reported the efficacy of drug delivery to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Borneol, a terpene from traditional Chinese medicine, sensitizes cells to TMZ by promoting HIF1α degradation, as demonstrated by Lin et al [ 88 ]. Previous studies have also shown that borneol enhances the efficacy of doxorubicin [ 134 ], curcumin [ 135 ], cisplatin [ 136 ], and radiotherapy [ 137 ]. Liu et al [ 79 ] demonstrated in preclinical studies the usefulness of mannose as an adjunct to TMZ and to enhance radiotherapy, and achieved long-term survival in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Borneol, a terpene from traditional Chinese medicine, sensitizes cells to TMZ by promoting HIF1α degradation, as demonstrated by Lin et al [ 88 ]. Previous studies have also shown that borneol enhances the efficacy of doxorubicin [ 134 ], curcumin [ 135 ], cisplatin [ 136 ], and radiotherapy [ 137 ]. Liu et al [ 79 ] demonstrated in preclinical studies the usefulness of mannose as an adjunct to TMZ and to enhance radiotherapy, and achieved long-term survival in mice.…”
Section: Discussionmentioning
confidence: 99%